Using Pattern Analysis and Systematic Randomness to Allocate U.S. Border Security Resources - Predd, Joel B.; Willis, Henry H.; Setodji, Claude Messan; Stelzner, Chuck (RAND Corporation, 2023)
This report investigates how the Office of Border Patrol could employ pattern and trend analysis and systematic randomness to increase interdiction rates and mitigate smuggler adaptation. The analysis shows how approaches that combine the techniques yield higher interdiction rates than approaches using either technique alone, and it examines the circumstances in which combined approaches are competitive with perfect surveillance.